Cerebral blood flow and Alzheimer's disease‐related biomarkers in cerebrospinal fluid in idiopathic normal pressure hydrocephalus. Issue 6 (27th March 2019) - Azuma, Shingo; Kazui, Hiroaki; Kanemoto, Hideki; Suzuki, Yukiko; Sato, Shunsuke; Suehiro, Takashi; Matsumoto, Takuya; Yoshiyama, Kenji; Kishima, Haruhiko; Shimosegawa, Eku; Tanaka, Toshihisa; Ikeda, Manabu
Abstract : Aim: Alzheimer's disease (AD) pathology is highly prevalent in patients with idiopathic normal pressure hydrocephalus (iNPH), and the presence of AD pathology may involve regional cerebral blood flow (rCBF). In this study, we examined the relationship between rCBF and AD‐related biomarkers in the cerebrospinal fluid of iNPH patients. Methods: Patients with iNPH ( n  = 39) were classified into groups with (iNPH/AD+) ( n =15) and without (iNPH/AD−) ( n =24) high biomarker probability of AD (i.e. combined low amyloid β 42 and high total tau in the cerebrospinal fluid). rCBF was quantified in 17 regions of interest by N‐isopropyl‐p‐[ 123 I]iodoamphetamine single‐photon emission computed tomography with the autoradiography method. We compared rCBF between the iNPH/AD− and iNPH/AD+ groups at baseline using a t ‐test and then compared changes in rCBF after shunt surgery between the groups using a paired t ‐test and two‐way repeated measures ANOVA. Results: At baseline, there were no significant differences in rCBF between the groups in most regions apart from the putamen. After shunt surgery, a significant increase in rCBF in the putamen, amygdala, hippocampus, and parahippocampal gyrus was observed in iNPH/AD− patients. In iNPH/AD+ patients, no significant improvement in rCBF was observed in any region. In repeated measures analysis of variance, a significant group × shunt interaction was observed in the parietal lobe, frontal lobe, posterior cingulate cortex, precuneus, lateral temporal lobe, amygdala, hippocampus, parahippocampal gyrus, and putamen. Conclusions: Improvement in rCBF after shunt surgery in iNPH/AD+ patients may be poorer than that in iNPH AD− patients.